2014
DOI: 10.1073/pnas.1313886111
|View full text |Cite
|
Sign up to set email alerts
|

G-protein coupled receptor BAI3 promotes myoblast fusion in vertebrates

Abstract: Muscle fibers form as a result of myoblast fusion, yet the cell surface receptors regulating this process are unknown in vertebrates. In Drosophila, myoblast fusion involves the activation of the Rac pathway by the guanine nucleotide exchange factor Myoblast City and its scaffolding protein ELMO, downstream of cellsurface cell-adhesion receptors. We previously showed that the mammalian ortholog of Myoblast City, DOCK1, functions in an evolutionarily conserved manner to promote myoblast fusion in mice. In searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 47 publications
(54 reference statements)
6
113
0
Order By: Relevance
“…We reexpressed Elmo1, since the exogenous MycElmo2 was difficult to express in Elmo2 siRNA-treated cells (the human Elmo2 SmartPool siRNA also targets murine mRNA). We also previously reported that biological functions of Elmo1 and Elmo2 in myoblast fusion are interchangeable (54). We observed that expression of Myc-Elmo1 in Elmo2 knockdown cells completely restored the invasion to an extent comparable to that for cells expressing a control siRNA (Fig.…”
Section: Elmo2 Is Required For Axl-induced Rac Activation Axl Promotsupporting
confidence: 69%
“…We reexpressed Elmo1, since the exogenous MycElmo2 was difficult to express in Elmo2 siRNA-treated cells (the human Elmo2 SmartPool siRNA also targets murine mRNA). We also previously reported that biological functions of Elmo1 and Elmo2 in myoblast fusion are interchangeable (54). We observed that expression of Myc-Elmo1 in Elmo2 knockdown cells completely restored the invasion to an extent comparable to that for cells expressing a control siRNA (Fig.…”
Section: Elmo2 Is Required For Axl-induced Rac Activation Axl Promotsupporting
confidence: 69%
“…Two laboratories recently made exciting discoveries regarding the functions of ADGRB1 (BAI1) and ADGRB3 (BAI3) in this system (Hochreiter-Hufford et al, 2013;Hamoud et al, 2014). Both proteins were reported to be expressed by myoblasts and to promote myoblast fusion into muscle fibers in vitro, but there appear to be differences regarding the in vivo context in which each protein functions, and these differences will be an interesting area for future study.…”
Section: Skeletal Muscle and Bonementioning
confidence: 99%
“…Indeed, the ICD of ADGRB1 (BAI1) forms a complex with ELMO (engulfment and cell motility) and Dock180 (dedicator of cytokinesis) and mediates phagocytosis of apoptotic cells and Gram-negative bacteria as well as myoblast fusion via an ELMO/Dock180/Rac signaling module (Park et al, 2007;Das et al, 2011Das et al, , 2014Hochreiter-Hufford et al, 2013). Similarly, BAI3 promotes myoblast fusion through ELMO/DOCK1 (Hamoud et al, 2014). A recent study showed that ADGRB1 (BAI1) also interacts with Par3/Tiam1 and recruits these proteins to synaptic sites for spinogenesis and synaptogenesis (Duman et al, 2013).…”
Section: B G Protein-independent Intracellular Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these protein interactions, Elmo proteins are ideal candidates to coordinate the activation of downstream effectors at the plasma membrane. For instance, the interaction of Elmo1/2 with BAI (brain-specific angiogenesis inhibitor) recruits them onto the proximal membrane to activate the small GTPase Rac1 through the Dock180 guanine nucleotide exchange factor to mediate engulfment of apoptotic cells or to promote muscle differentiation (5,6). In addition, Elmo2 has been implicated in Akt activation, probably through the interaction with small GTPases, such as RhoG (9 -11).…”
mentioning
confidence: 99%